Stable Chitosan-Based Nanoparticles Using Polyphosphoric Acid or Hexametaphosphate for Tandem Ionotropic/Covalent Crosslinking and Subsequent Investigation as Novel Vehicles for Drug Delivery - Saeed, Ramzi Mukred; Dmour, Isra; Taha, Mutasem O. (Frontiers in Bioengineering and Biotechnology, 2020)
Chitosan nanoparticles (NPs) are widely studied as vehicles for drug, protein, and gene delivery. However, lack of sufficient stability, particularly under physiological conditions, render chitosan NPs of limited pharmaceutical utility. The aim of this study is to produce stable chitosan NPs suitable for drug delivery applications. Chitosan was first grafted to phthalic or phenylsuccinic acids. Subsequently, polyphosphoric acid (PPA), hexametaphosphate (HMP), or tripolyphosphate (TPP) were used to achieve tandem ionotropic/covalently crosslinked chitosan NPs in the presence of 1-ethyl-3-(3-dimethylaminopropyl)-carbodiimide (EDC). Thermal and infrared traits confirmed phosphoramide bonds formation tying chitosan with the polyphosphate crosslinkers within NPs matrices. DLS and TEM size analysis indicated spherical NPs with size range below 350 nm. The generated NPs exhibited excellent stabilities under harsh pH, CaCl2, and 10% FBS conditions. Interestingly, DLS, NPs stability and infrared data suggest HMP to reside within NPs cores, while TPP and PPA to act mainly as NPs surface crosslinkers. Drug loading and release studies using methylene blue (MB) and doxorubicin (DOX) drug models showed covalent PPA- and HMP-based NPs to have superior loading capacities compared to NPs based on unmodified chitosan, generated by ionotropic crosslinking only or covalently crosslinked by TPP. Doxorubicin-loaded NPs were of superior cytotoxic properties against MCF-7 cells compared to free doxorubicin. Specifically, DOX-loaded chitosan-phthalate polyphosphoric acid-crosslinked NPs exhibited 10-folds cytotoxicity enhancement compared to free DOX. The use of PPA and HMP to produce covalently-stabilized chitosan NPs is completely novel.